Subjective well-being among individuals with Down syndrome - Íris Björk Indriðadóttir 1996- (2019)
Subjective well-being (SWB) can be defined as how people evaluate their lives and own emotional experiences. SBW is a broader term than happiness and refers to all different forms of evaluation of one‘s life or emotional experiences, such as happiness, life satisfaction and positive affect. An important part of life satisfaction and well-being, particularly when researched among individuals with an intellectual disability, is that individualistic perceptions and values are essential. They are considered as key aspects of quality of life by virtually all contemporary researchers. This study’s aim was to research the SWB of individuals with Down syndrome (DS) and compare the results to individuals without the syndrome. Individuals with DS, who were at least 18 years old, were asked questions from standard scales to measure life satisfaction and happiness. To compare, the same questions were presented to control samples of individuals without DS. The same questionnaires were presented to participants of both groups in an attempt to reach a conclusion. Researchers hypothesised that individuals with DS were satisfied with their lives and that they were just as happy, if not happier, than other individuals. The research confirmed both hypotheses as individuals with DS were very satisfied with their lives and significantly happier than non-DS individuals. Hamingja og lífsánægja hefur verið skilgreind sem það hvernig einstaklingar meta líf sitt og upplifanir. Mikilvægt atriði er varðar lífsánægju þegar hún er rannsökuð meðal einstaklinga með þroskahömlun, er að upplifun og gildi hvers og eins einstaklings skiptir mestu máli. Markmið þessarar rannsóknar var að skoða hamingju og lífsánægju einstaklinga með Downs-heilkenni og bera saman við aðra einstaklinga sem ekki hafa heilkennið. Þátttakendur voru einstaklingar með Downs-heilkenni sem voru 18 ára eða eldri. Spurningarlistinn samanstóð af spurningum úr stöðluðum spurningarlistum sem mæla hamingju og lífsánægju. Sami spurningarlistinn var lagður fyrir samanburðarhóp ...